1994
DOI: 10.1002/bjs.1800810627
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome allele loss in colorectal liver metastases and its association with clinical features

Abstract: Molecular genetic changes are better characterized in colorectal carcinoma than in other common adult tumours. Consistent allele losses, or loss of heterozygosity (LOH), on chromosomes 5q, 17p and 18q have been well established. These changes are associated with the prognosis of the disease. Little is known of such changes in liver metastases of colorectal origin. The extent of allelic loss and its association with clinical features were investigated in 19 patients with colorectal liver metastases by using 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…These tumours display distinctive clinicopathological features, including a tendency to be located in the right colon, associations with other neoplasms, a younger age at presentation, a high grade or medullary type, mucinous differentiation, and peritumoural ('Crohn's like') lymphoid infiltration. MSI status is also associated with an earlier stage at presentation and less nodal involvement compared with MSS tumours (25).…”
Section: Discussionmentioning
confidence: 94%
“…These tumours display distinctive clinicopathological features, including a tendency to be located in the right colon, associations with other neoplasms, a younger age at presentation, a high grade or medullary type, mucinous differentiation, and peritumoural ('Crohn's like') lymphoid infiltration. MSI status is also associated with an earlier stage at presentation and less nodal involvement compared with MSS tumours (25).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have consistently identified a higher frequency of liver metastases in CRC tumours displaying complex karyotypes (tumours with more than three chromosomal abnormalities) bearing a loss of heterozygosity in chromosomes 5q 35, 36, 14q 37, 17p 35, 36, 18q 32, 35, 36, and 22q 36; losses of chromosomes 8p (59%), 1p (56%), and 18p (48%); and gains/amplification of chromosomes 13q (48%), 7p (44%), 8q (44%), and 20q (85%)—including amplification of 20q13 (38%) 32, 35. In agreement with these observations, all of our metastatic tumours showed complex karyotypes with seven or more altered chromosomes; at the same time, additional abnormalities were also observed in metastatic tumours for a large number of the above chromosomes (chromosomes 3, 7, 8, 9, 13, 17, and 20 in the whole series, and chromosomes X and Y in males).…”
Section: Discussionmentioning
confidence: 99%
“…12 Three candidate tumor-suppressor genes, DCC, DPC4 and JV181, are located in this region. 20,21 Loss of 18q is associated with poor clinical outcome or metastases in colorectal cancer [22][23][24] and cervical squamous-cell carcinoma. 25 Chromosome arm 8q23-24 contains the candidate gene C-MYC, whose activation is a common event in various types of neoplasia and has been associated with different cellular processes relevant to the transformation of cancer cells to malignancy.…”
Section: Discussionmentioning
confidence: 99%